Study of platelet indices in dengue fever with thrombocytopenia and correlation of immature platelet fraction (IPF) with platelet recovery - Ahmad Wayez; Lubna Zafar; Mohsin Aijaz; Nishat Afroz (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
Dengue fever is the most rapidly spreading mosquito-borne viral disease in the world. An estimated 50 million infections per year occur across approximately 100 countries. The incidence has increased 30-fold with increasing geographic expansion with potential for further spread [1].